Analysis of Gender Equality and Disability Inclusion: Based on The Sustainability Report of Goto And The ESGReport of Grab In 2022 - Ibrahim, Rizka Zamzani; Utha, Maria Ariesta; Kurniawati, Kurniawati (Green Publisher Indonesia, 2023)
Amidst the changing times reflected in the rapid growth of the information technology industry in Indonesia driven by technology startups, there are still challenges regarding gender equality and disability inclusion. Data shows an increase in women's participation in technology, but their representation in leadership positions remains low. Additionally, people with disabilities still face barriers to entering this sector. Major companies like GoTo and Grab are paying attention to the importance of these issues and are starting to implement them in their operations, as depicted in the Sustainability Report of GoTo and the ESG Report of Grab for the year 2022. This research employs a qualitative descriptive approach to analyze these reports, focusing on gender equality and disability inclusion. The results are expected to provide insights into how major technology companies in Indonesia perceive and address issues of equality and inclusion.